2017
DOI: 10.1088/1361-6587/aa8378
|View full text |Cite
|
Sign up to set email alerts
|

Experimental benchmark of kinetic simulations of capacitively coupled plasmas in molecular gases

Abstract: We discuss the origin of uncertainties in the results of numerical simulations of low-temperature plasma sources, focusing on capacitively coupled plasmas. These sources can be operated in various gases/gas mixtures, over a wide domain of excitation frequency, voltage, and gas pressure. At low pressures, the non-equilibrium character of the charged particle transport prevails and particle-based simulations become the primary tools for their numerical description. The particle-in-cell method, complemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…At the end of the 90s, a standardized RF discharge experiment -socalled, GEC Reference Cell [320] was also specifically designed for validation and is still used as shown in the recent study performed in Ref. [321]. Recently, there has been different works on the benchmarking of codes.…”
Section: State Of the Art And Recent Progressmentioning
confidence: 99%
“…At the end of the 90s, a standardized RF discharge experiment -socalled, GEC Reference Cell [320] was also specifically designed for validation and is still used as shown in the recent study performed in Ref. [321]. Recently, there has been different works on the benchmarking of codes.…”
Section: State Of the Art And Recent Progressmentioning
confidence: 99%
“…Our model of the oxygen CCPs is largely based on the "xpdp1" set of elementary processes [73] and its recent revision [74], and is the same as described in our previous works [65,66,69]. Therefore, only a brief summary of the features of the model is given below and the reader is referred to [65] for details.…”
Section: Model Of Oxygen Ccps and Computational Implementationmentioning
confidence: 99%
“…The code allows including the emission of secondary electrons from the electrodes; we use SEEC values of γ = 0 (disregard electron emission), γ = 0.06 (a value that is characteristic for metal surfaces), and γ = 0.4 (a value typical for dielectric surfaces). The gas temperature is fixed at T g = 350 K. For the surface quenching probability of O 2 (a 1 ∆ g ) singlet delta molecules we use the value of α = 6 × 10 −3 , which resulted in our previous studies in a good overall agreement between the experimental and simulation data for the ion fluxes and the ion flux-energy distribution functions at the electrodes [65,66,69]. In the cases when a DC self-bias voltage develops, its value is determined in an iterative manner to ensure equal losses of positive and negative charges at each electrode over one period of the fundamental driving frequency [31].…”
Section: Model Of Oxygen Ccps and Computational Implementationmentioning
confidence: 99%
“…Recent work includes sensitivity analysis of input model parameters on oxygen RF discharges by varying collision cross sections and surface quenching parameters [12]. In this study, secondary emission coefficients were also varied in a CF 4 -Ar discharge that demonstrated the sensitivity of the sheath to this parameter.…”
Section: Introductionmentioning
confidence: 96%